Perencaanaan dan Proses Pemasaran yang Dilakukan Xpander - Natasya Azahara; Hendra Riofita (Populer: Jurnal Penelitian Mahasiswa, 2024)
Effective marketing planning is the key to success for companies, especially in the increasingly competitive automotive industry. This research aims to analyze the planning and marketing process carried out by Mitsubishi Xpander. The method used is a literature review, which involves analyzing various reference sources related to marketing and business strategy. The findings show that Mitsubishi Xpander has successfully implemented a planned marketing strategy, including product adjustments, competitive prices and effective promotions. Additionally, in-depth market analysis helps companies in understanding consumer preferences and identifying opportunities in the market. The implications of this research highlight the importance of implementing marketing strategies that are adaptive and responsive to changing consumer trends to increase competitiveness and business sustainability. The results of this research can provide insight for other companies in formulating more effective and efficient marketing strategies.